PINDAR ΙΣΧΝΟΦΩΝΟΣ (SCHOL. IN PI. O. 6.88). (6th December 2017) - Bartol, Krystyna
Abstract : I argue in this article that the scholiast's claim (schol. in Pi. O. 6.88) that Pindar was ἰσχνόφωνος meant that he was believed to be a stammerer rather than a weak-voiced person. I have attempted to show how later commentators developed some points of Alexandrian critics' judgement of Pindar's poetry into a conventional biographical reference to the poet's speech defect.